Plant Regeneration And Biochemical Changes in Rice (Oryza Sativa L.) Under NaCl Stress - Khan Khattak, Mohammad Saeed (1996)
This project was designed to examme the effects of NaCI on growth and regeneration of callus and cell suspension cultures of the five rice cultivars namely, Puteh Perak, Mahsuri, Basmati-370, Nona Bokra and Khari Gunja. In addition, changes of nitrogen assimilating enzymes, phosphatase and some dehydrogenase of Kreb's Cycle in cell suspension cultures of Basmati-370 and Puteh Perak were also investigated. The callus cultures were induced from embryo section of seeds of rice using MS solid media containing 10 µM 2,4-D and 2 µM kinetin. Cell suspension cultures were initiated in liquid media from the induced embryogenic callus of rice using salts of the B5 media containing 10 µM 2,4-D. The five rice cultivars tested had high rates of callus induction (80-88%). In the one step NaCI treatment, the growth of control callus and cell suspension cultures of the five rice cultivars decreased and significant morphological changes were observed. At 180 mM NaCI treatment , the reduction in callus growth was 29, 36, 42, 32 and 42% while at 70 mM NaCl, reduction in the growth of cell suspension culture was 38, 53, 58, 41 and 55% in Puteh Perak, Mahsuri, Basmati-370, Nona Bokra and Khari Gunj a, respectively compared to the control culture without NaCI (100%). The callus growth was completely retarded at 540 mM NaCI treatment while in cell suspension it was at 210 mM NaCl. The multiple step NaCl-treated callus and cell suspension cultures of the five rice cultivars produced higher growth (% dry weight) in the presence of NaCI compared to the control cultures. The callus and cell suspension of the five rice cultivars on high NaCl containing media reached a maximum growth at range of 10-1 3th passages and 6-9th passages, respectively while the control cultures proliferated at constant rate. The multiple step NaCl-treated cell suspension of Basmati:J70 showed stability to NaCI treatment compared to the control. MS solid regeneration media containing 3 /-lM lAA and 40 /-lM kinetin was most suitable for plant regeneration of callus and cell suspension of five rice cultivars. The plant regeneration capacity of one step NaCl-treated callus and cell suspension cultures of the five rice cultivars decreased with the increased concentrations of NaCI in the treatment media. Higher regeneration frequencies were observed from multiple step NaCl-treated callus of Puteh Perak, Mahsuri and Nona Bokra and cell suspension cultures of Puteh Perak and Nona Bokra compared to the control while lower regeneration than the control was obtained in other cultivars. The plant regeneration capacity of multiple step NaCl-treated and control cultures decreased with the increase in culture age. However, NaCl-treated cultures maintained higher regeneration capacity for up to 48 weeks of culture compared to the control. The growth rate of cell suspension of Basmati-370 increased from day 4 up to day 1 0 and the activities of ACP, ALP, GS, MDH, NADP-ICDH and SDH were highest on day 10 while GDH and GOGAT on day 8 and NR on day 6 during the 14 days of culture period. The activities of GDH, GOGAT, NR, ACP, ALP, MDH and NADP-ICDH extracted from NaCI-treated cell suspension of Basmati-3 70 increased while GS and SDH activities decreased. The activities of GDH, NR, ALP and MDH decreased in cell suspension of Puteh Perak but increased in Basmati-370 under increasing NaCI treatments. The GS and SDH activities increased in the presence of NaCI of Puteh Perak but decreased in Basmati-370 and the GOGAT, ACP and NADPICDH increased by NaCI in both cultivars tested. The addition of NaCI (0-200/-lM) to the assay mixture resulted in increased specific activities of GDH, NR, GOGAT, ACP, MDH and NADP-ICDH at low concentration but decreased the activities at high concentrations while the specific activities of GS, ALP and SDH continously decreased. Changes in selected enzyme activities of cell suspension of rice due to NaCI indicates that NaCl interferes with nitrogen and phosphorus metabolism.